2013
DOI: 10.4066/amj.2013.1676
|View full text |Cite
|
Sign up to set email alerts
|

Perhaps we don’t know what we thought we knew: Why clinicians need to re-visit and re-engage with clinical anatomy

Abstract: EDITORIALPlease cite this paper as: Cornwall J. Perhaps we don't know what we thought we knew: Why clinicians need to re-visit and re-engage with clinical anatomy. AMJ 2013, 6, 6, 339-340. http//dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Teaching the gross anatomy of complex structures such as the anterior optic pathways to students is a challenging task [ 26 ] and some authors have suggested that clinical anatomy should be continuously reappraised in light of the findings of the newest research methods [ 27 ]. In particular, three-dimensional (3D) visualizations offered by DTI tractography can be used not only for clinical assessment but also for teaching complex anatomy, based on both standard atlas representations and individual variation (as shown in Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Teaching the gross anatomy of complex structures such as the anterior optic pathways to students is a challenging task [ 26 ] and some authors have suggested that clinical anatomy should be continuously reappraised in light of the findings of the newest research methods [ 27 ]. In particular, three-dimensional (3D) visualizations offered by DTI tractography can be used not only for clinical assessment but also for teaching complex anatomy, based on both standard atlas representations and individual variation (as shown in Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that clinicians either say they require least Anatomy or they diagnose with overconfidence of without knowing necessary and sufficient Anatomy. The clinicians guiding/exercising clinical Anatomy for clinical analysis often have neither the time to update anatomical knowledge nor remember it to the required level as "Perhaps we don't know what we thought we knew: Why clinicians need to revisit and re-engage with clinical anatomy" [8]. Specialty practitioners dealing with more critical patients suffering from more complex and advanced diseases, certainly, require more precise diagnosis to explore macro/microstructural distortion/deformation to be manipulated by medicines.…”
Section: Diagnosismentioning
confidence: 99%
“…'Work in progress' describes areas where anatomical knowledge remains incomplete and/or controversial and includes acquiring a more detailed understanding of the anatomy of the extremes of age; resolving or refining disputed descriptions of regional anatomy, such as the pelvic floor (unifying the differing perspectives of colorectal and urological surgeons, obstetricians and radiologists) and the cervical deep fascia; updating anatomical terminology with reference to consensus papers produced by surgical groups and attitudinally correct cardiac terminology; acknowledging that textbooks tend to describe the youthful anatomical average, embracing evidence-based anatomy and undertaking meta-analyses of anatomical databases (Cornwall, 2013;Roy et al 2015); recognising the ranges of normal anatomical variation, e.g. in assessing dermatome distribution in the lower limb (Lee et al 2008) or the prevalence of vascular variations (Schmidt et al 2008).…”
Section: What Now?mentioning
confidence: 99%